Bilateral corneal ulcer in an old man with pemphigus vulgaris - Tania Yelina Silva Chil; Danay Duperet Carvajal; Guadalupe Rinconcillo Medellín (Centro Provincial de Información de Ciencias Médicas, 2019)
The case report of a 72 years patient is described, with diagnosis of pemphigus vulgaris who went to the Ophthalmology Service of Dr. Juan Bruno Zayas Alfonso Teaching General Hospital in Santiago de Cuba because he suffered from ocular redness, together with a decrease vision and abundant secretions of approximately 5 days of history. In the ophthalmological examination the presence of bilateral corneal ulcer was confirmed due to infectious perforation. Treatment was indicated with antibiotic eyewashes (ceftazidime and amikacine), non esteroidal anti-inflammatory drugs, antihypertensive agents and contact lens, with which the injuries of both eyes improved. The infectious process could be due to certain susceptibility to the steroids and systemic inmunosupressors, as therapy associated with pemphigus vulgaris, or to the autoinmune mechanism characterizing this dermatopathy.